Lessons from five decades of experimental and behavioral research on accountability: A systematic literature review - Aleksovska, M.; Schillemans, T.; Grimmelikhuijsen, S.G. (My University, 2019)
The study of accountability in public administration has developed largely in parallel to the study of accountability in the behavioral sciences. In an effort to bridge this divide, we present a systematic review of the experimental literature on accountability in the behavioral sciences and draw lessons for public administration. We summarize the findings of 266 experiments exploring the effects of accountability mechanisms, presented in 211 articles published between 1970 and 2016. These findings are organized in four broad themes: effects of accountability on decision-making, behavior, and outcomes; and effects of the specific characteristics of accountability mechanisms. The review shows numerous desirable effects of accountability on individual decision-making and behaviors. This is of high relevance to public administration studies on accountability as it sheds light on causal mechanisms and allows for a balanced perspective on positive and negative effects of various types of accountability mechanisms. It is however not always possible to translate findings from behavioral research directly to public administration settings. We discuss the meaning and value of our findings for public administration studies and develop an agenda for future behavioral research on public sector accountability.
Keywords: accountability; experiments; systematic review; decision-making